GREEN SYNTHESIS OF MAGNETIC IRON NANOPARTICLES USING MEDICINAL PLANT TRIDAX PROCUMBENS LEAF EXTRACTS AND ITS APPLICATION AS AN ANTIMICROBIAL AGENT AGAINST E. COLI - PATIL, YOJANA Y.; SUTAR, VAISHNVI B.; TIWARI, ARPITA P. (International Journal of Applied Pharmaceutics, 2020)
Objective: The present study was aimed at the biological synthesis of magnetic iron nanoparticles by using the plant extract of Tridax procumbens and also to study their antimicrobial property against gram-negative bacteria (Escherichia coli). Methods: The synthesis of magnetic iron nanoparticles was carried out by the co-precipitation method using biological methods like plant extract as reducing agent and capping agents are biocompatible and non-hazardous. These nanoparticles were characterized by UV-Visible spectroscopy, XRD (X-Ray Diffraction), and SEM (Scanning Electron Microscope). As well as antibacterial activity of the nanoparticles was carried out by agar well diffusion method and Most Probable Number (MPN) method against gram-negative E. coli (Escherichia coli) bacteria. Results: The average crystallite size of Magnetic Nanoparticles (MNPs) was found to be 72 nm by X-ray diffraction. The optical absorption band at wavelengths of 240 nm and 402 nm was obtained from the UV Visible spectrum. Spherical shape morphology was observed in SEM studies. The antibacterial assay clearly expressed that E. coli showed a maximum zone of inhibition (15±0.15 mm) at 2 mg/ml and 1 mg/ml concentration was found for Magnetic Nanoparticles. In the Most Probable Number (MPN) test it is seen that the bacterial count is reduced after adding synthesized NPs into the water sample. Conclusion: The results of the present study conclude that the Magnetic Nanoparticles synthesized using Tridax procumbens leaf extracts is found to be stable and show good antibacterial activity against gram-negative (Escherichia coli) bacteria.